Pengaruh Pemahaman Akuntansi, Pemanfaatan Sistem Informasi Akuntansi, dan Sistem Pengendalian Intern Terhadap Kualitas Laporan Keuangan Pemerintah Daerah: Studi Kasus pada Pemerintah Dearah Kabupaten Banyuasin, Musi Banyuasin, dan Ogan Ilir - Dewi Kartika Sari; Sri Hartaty; Yuliana Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of accounting understanding, utilization of accounting information systems, and internal control system on the quality of local government financial report in Banyuasin, Musi Banyuasin, and Ogan Ilir Regencies. The data of this study uses primary data with a quantitative approach. This study uses a convenience sampling method. The population in this study were all employees of the Regional Financial and Asset Management Agency of Banyuasin, Musi Banyuasin, and Ogan Ilir Regencies. The sample uses in this study was 51 respondents. The analysis technique used to test the research hypothesis was multiple linear regression analysis with the help of SPSS software version 26. The results of this study indicate that the variables of accounting understanding does not have a significant effect on the quality of local government financial reports. Meanwhile, the utilization of accounting information system and internal control systems has a positive and significant effect on the quality of local government financial reports. Simultaneous tests show that the variables of accounting understanding, utilization of accounting information systems, and internal control systems simultaneously affect the quality of financial reports.